2010
DOI: 10.1242/jeb.037184
|View full text |Cite
|
Sign up to set email alerts
|

When surfacers do not dive: multiple significance of extended surface times in marine turtles

Abstract: SUMMARYMarine turtles spend more than 90% of their life underwater and have been termed surfacers as opposed to divers. Nonetheless turtles have been reported occasionally to float motionless at the surface but the reasons for this behaviour are not clear. We investigated the location, timing and duration of extended surface times (ESTs) in 10 free-ranging loggerhead turtles (Caretta caretta) and the possible relationship to water temperature and diving activity recorded via satellite relay data loggers for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 53 publications
3
66
0
Order By: Relevance
“…Our Wndings extend those reported for juvenile loggerhead turtles tracked from the Bay of Naples, one of which entered the Adriatic (Hochscheid et al 2010). In this respect, the case of turtle G is particularly informative, since it performed seasonal migrations shuttling between two distant foraging grounds and showed Wdelity to a speciWc north Adriatic foraging ground.…”
Section: Discussionsupporting
confidence: 79%
“…Our Wndings extend those reported for juvenile loggerhead turtles tracked from the Bay of Naples, one of which entered the Adriatic (Hochscheid et al 2010). In this respect, the case of turtle G is particularly informative, since it performed seasonal migrations shuttling between two distant foraging grounds and showed Wdelity to a speciWc north Adriatic foraging ground.…”
Section: Discussionsupporting
confidence: 79%
“…In general, resident areas of juveniles in oceanic zones are much wider than in neritic zones (Revelles et al 2007b;Cardona et al 2009;Casale et al 2012aCasale et al , 2012b (Figure 4), as also observed for adults in the Mediterranean and elsewhere (Hawkes et al 2006;Schofield et al 2010a). Long-term residence of juveniles in neritic foraging grounds seems more common than in oceanic areas and it has been observed in various locations through tag returns (Casale et al 2007a;Revelles et al 2008) and satellite tracking Cardona et al 2009;Hochscheid et al 2010;Casale et al 2012aCasale et al , 2012bHochscheid et al 2013) (Figure 3). The juvenile neritic foraging sites are, however, usually larger than the adult neritic sites, with juveniles showing a propensity to wander over quite large areas (e.g.…”
Section: Large Juvenilesmentioning
confidence: 98%
“…Some just wandered across wide areas, with no sign of residence at any specific site (Bentivegna 2002;Casale et al 2007a;Eckert et al 2008;Cardona et al 2009;Hochscheid et al 2010) (Figure 3). Others frequented somewhat smaller areas (Cardona et al 2005;Revelles et al 2007aRevelles et al , 2007bEckert et al 2008;Cardona et al 2009;Hochscheid et al 2010;Casale et al 2012aCasale et al , 2012b (Figure 3), in some cases remaining for a long time in very restricted sites (Hochscheid et al 2010;Mencacci et al 2011). The areas frequented and the routes followed are the result of a combination of surface circulation patterns and the turtles' active swimming Revelles et al 2007b).…”
Section: Large Juvenilesmentioning
confidence: 99%
“…Apart from behavioural means (Hochscheid et al, 2010), chelonid sea turtles generally do not thermoregulate and, hence, do not spend energy for thermoregulatory purposes. Leatherback turtles, on the other hand, might use the metabolic heat generated by vigorous swimming activity to maintain an elevated and stable body temperature (Bostrom and Jones, 2007;Bostrom et al, 2011).…”
Section: Respiratory Frequency (F R )mentioning
confidence: 99%
“…One possible complication in this context is the basking behaviour occasionally observed in marine turtles. For loggerhead turtles, it was suggested that periods spent basking at the surface have a re-warming function to compensate for decreased body temperatures when diving in cooler water, possibly to enhance digestive function (Hochscheid et al, 2010). While ambient temperature is monitored by the acceleration data logger and was included in our model, it is not clear how well such temperature measurements will represent turtle body temperature (affecting turtle metabolism) under these circumstances.…”
Section: Respiratory Frequency (F R )mentioning
confidence: 99%